Musical instruments, songs and dances of the Chokwe (Dundo region, Lunda district, Angola) - Bastin, Marie-Louise (International Library of African Music, 1992)
During my stay with the Chokwe in 19561 swam in an atmosphere of music and dance, in the most varied circumstances, and always in an ambience permeated by sensitivity, earnestness and excitement. This matrilineal bantu people, originating from central Angola, live for the most part today in the northeast of Angola, spilling into Zaire and Zambia since the end of last century. Despite this expansion, Chokwe culture remains fundamentally homogeneous, with local variations, however, due to the extent of the territory which the more than 600,000 of them occupy. I shall speak only of traditional music and choreography because for a good forty years new styles have been spread among young Chokwe through the radio.
Keywords: Chokwe (African people); Musical instruments; Music; Dance; Songs; African Music; Angola